A PCR-based method for the diagnosis of Enterobius vermicularis in stool samples, specifically designed for clinical application - Ummarino, Aldo; Caputo, Michele; Tucci, Francesco Antonio; Pezzicoli, Gaetano; Piepoli, Ada; Gentile, Annamaria; Latiano, Tiziana; Panza, Anna; Calà, Nicholas; Ceglia, Antonio Pio; Pistoio, Giovanni; Troiano, Vincenzo; et al. (Frontiers in Microbiology, 2022)
Background. Enterobius vermicularis (E. vermicularis) is a nematode that infects up to 200 million people worldwide, despite effective medications being available. Conventional diagnostic tests are hindered by low sensitivity and poor patient compliance. Furthermore, no biomolecular techniques are available for clinical application. The aim of this study was to develop a procedure specifically designed for clinical application to detect E. vermicularis by means of polymerase chain reaction (PCR). Materials and Methods. Two subject groups were taken into account: a group of 27 infected patients and a control group of 27 healthy subjects. A nested-PCR was performed on faecal samples to detect E. vermicularis. Due to the intrinsic difficulties of the faecal matrix, several countermeasures were adopted to ensure the efficient performance of the method: a) a large amount of faeces for the extraction process (20 grams instead of 200 mg); b) a combination of chemical and physical treatments to grind the faecal matrix; c) an additional purification process for the negative samples after the first nested-PCR; d) the selection of a very specific target region for the PCR. Results. Due to the lack of overlap with other organisms, a sequence of the 5S ribosomal DNA (rDNA) spacer region including the tract SL1 was chosen to design appropriate external and internal primers. The first nested-PCR detected E.vermicularis in 19/27 samples from infected patients. After further purification, 5/8 of the negative samples resulted positive at the second PCR. Conversely, all the samples from healthy controls resulted negative to both PCR. Sensitivity and specificity of the method were respectively 88.9% and 100%. Conclusions. The results prove the high diagnostic accuracy of the proposed method, addressing and overcoming the challenges posed by both conventional tests and PCR-based approaches. Therefore, the method can be proposed for clinical application.